2019
DOI: 10.5114/hpr.2019.87934
|View full text |Cite
|
Sign up to set email alerts
|

Internalizing and externalizing behaviors in chronically ill adolescents in the context of family system functioning

Abstract: health psychology report • volume 7(3), 9 original article background Diagnosis of chronic illness, which constitutes a lifethreatening situation such as in Marfan syndrome or disease with periods of remission and severity such as in juvenile idiopathic arthritis (JIA), leads to problems with the functioning of the adolescent and the whole family system. Therefore the aim of the study was to determine the differences in severity of internalizing and externalizing problems and in the perception of the family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Studies have shown that the prevalence of psychiatric disorders is higher among people with chronic illness than in the general population (Trawicka, 2019). Additionally, chronic physical health conditions are risk factors for behaviours problems (Barlow & Ellard, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the prevalence of psychiatric disorders is higher among people with chronic illness than in the general population (Trawicka, 2019). Additionally, chronic physical health conditions are risk factors for behaviours problems (Barlow & Ellard, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies describing the behavior of people with chronic disease show differences in the level of internalizing and externalizing behavior between the groups affected by the disease and those in the control group. 18 This approach allows a better understanding of the psychosocial functioning of people with chronic illness and makes it possible to develop therapeutic strategies based on this knowledge. In this study, it was decided to look at internalizing and externalizing behaviors from the perspective of predictors.…”
Section: Discussionmentioning
confidence: 99%
“…Physical illness, including chronic medical conditions that require long-term treatment, can increase the risk of EBPs [29,30]. Young people with such illnesses are more likely to have higher levels of both internalizing and externalizing problems [31][32][33][34][35][36]. This may be due to a perceived lack of control over the illness and its symptoms, restrictions to participate in positive activities, and side effects of treatments.…”
Section: Introductionmentioning
confidence: 99%